Microbes of biotechnological importance in acidic saline lakes in the Yilgarn Craton, Western Australia - Boase, Katelyn; Santini, Talitha; Watkin, Elizabeth (Frontiers in Microbiology, 2024)
Acidic salt lakes are environments that harbor an array of biologically challenging conditions. Through 16S rRNA, 18S rRNA and ITS amplicon sequencing of eight such lakes across the Yilgarn Craton of Western Australia, we aim to understand the microbial ecology of these lakes with a focus on iron and sulfur oxidizing and reducing microorganism that have theoretical application in biomining industries. In spite of the biological challenges to life in these lakes, the microbial communities were highly diverse. Redundancy analysis of soil samples revealed sulfur, ammonium, organic carbon and potassium were significant divers of the microbial community composition. The most abundant microbes with a hypothetical application in biomining include the genus 9M32 of the Acidithiobacillus family, Alicyclobacillus and Acidiphilium all of which are possible iron and/or sulfur oxidizing bacteria. It is evident through this study that these lakes harbor multiple organisms with potential in biomining industries that should be exploited and studied further.